2010
DOI: 10.1007/s11270-010-0528-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating Asymmetry of Chironomus spp. (Diptera: Chironomidae) Larvae in Association with Water Quality and Metal Pollution in Permatang Rawa River in the Juru River Basin, Penang, Malaysia

Abstract: The levels of fluctuating asymmetry [random differences between symmetric organismal traits, fluctuating asymmetry (FA)] in the fourth instar of Chironomus spp. larvae inhabiting an agrochemical polluted river [Permatang Rawa River (PRR)] in the Juru River Basin, northeastern peninsular Malaysia, were measured. The PRR receives waters primarily from adjacent rice fields which are exposed to fertilizer and pesticide residues. Samples of larvae, water, and sediments were collected monthly from November 2007 to J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 54 publications
0
8
1
Order By: Relevance
“…It is known that sediments can serve as a carrier of many metals and toxic compounds, e.g., Pb, Cd, Zn, Cu, Al, Fe, Mn, Cr, and Ni (see e.g., Novotny and Chesters 1989;Kundell and Rasmussen 1995). Rivers contaminated by metals and organic substances have often been reported to be associated with an increased incidence of phenotypic defects, such as phenodeviation and fluctuating asymmetry (FA), particularly in invertebrates (Al-Shami et al 2011;Bonada and Williams 2002;Groenendijk et al 1998;Arambourou et al 2014). Deposition of organic sediments can result in anaerobic conditions in rivers and streams by increasing the sediment oxygen demand (SOD) (Kundell and Rasmussen 1995).…”
Section: Reproduction and Epigeneticsmentioning
confidence: 99%
“…It is known that sediments can serve as a carrier of many metals and toxic compounds, e.g., Pb, Cd, Zn, Cu, Al, Fe, Mn, Cr, and Ni (see e.g., Novotny and Chesters 1989;Kundell and Rasmussen 1995). Rivers contaminated by metals and organic substances have often been reported to be associated with an increased incidence of phenotypic defects, such as phenodeviation and fluctuating asymmetry (FA), particularly in invertebrates (Al-Shami et al 2011;Bonada and Williams 2002;Groenendijk et al 1998;Arambourou et al 2014). Deposition of organic sediments can result in anaerobic conditions in rivers and streams by increasing the sediment oxygen demand (SOD) (Kundell and Rasmussen 1995).…”
Section: Reproduction and Epigeneticsmentioning
confidence: 99%
“…Fluctuating Asymmetry (FA) refers to random and subtle departure from a perfect bilateral symmetry [24]. It has also been repeatedly shown that levels of FA in chironomid larvae [6], [9], [25], are higher when exposed to pollution. However, the response seems to depend largely on the studied trait [12].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the effects on morphology, metal pollution may induce morphological deformities [28], the increase in developmental instability [29,30], and reduced body size [6,31]. Generally, three mechanisms may underline the negative impact of metals on the body size/mass: (1) toxicity of metals based on the displacement of the essential metals from enzymes at active sites, resulting in loss of their function, (2) trade-offs between the cost of detoxication and energy allocation to growth and development [6,32], and (3) limited food availability in contaminated areas [7].…”
Section: Discussionmentioning
confidence: 99%